2012
DOI: 10.1152/ajplung.00064.2011
|View full text |Cite
|
Sign up to set email alerts
|

Apocynin improves oxygenation and increases eNOS in persistent pulmonary hypertension of the newborn

Abstract: RH. Apocynin improves oxygenation and increases eNOS in persistent pulmonary hypertension of the newborn. Am J Physiol Lung Cell Mol Physiol 302: L616 -L626, 2012. First published December 23, 2011 doi:10.1152/ajplung.00064.2011.-NADPH oxidase is a major source of superoxide anions in the pulmonary arteries (PA). We previously reported that intratracheal SOD improves oxygenation and restores endothelial nitric oxide (NO) synthase (eNOS) function in lambs with persistent pulmonary hypertension of the newborn (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 47 publications
2
28
0
Order By: Relevance
“…In the current study, we found an increase in expression of the superoxide generating isoform Nox2, but not Nox1, in PPHN PA and PASMC. We previously reported increased expression of the Nox2 activating protein p67 phox in fetal PPHN lambs relative to fetal controls (7), and we recently demonstrated that apocynin, an inhibitor of leukocyte Nox2 and a scavenger of H 2 O 2 in vitro (18), decreased p22 phox and p47 phox expression in ventilated PPHN lambs (46). While superoxide generated by Nox2 can contribute to elevated H 2 O 2 in PPHN, our siRNA data suggest that Nox4 is the major source of increased ROS in PPHN PASMC.…”
Section: Nox4 In Pphnmentioning
confidence: 97%
See 1 more Smart Citation
“…In the current study, we found an increase in expression of the superoxide generating isoform Nox2, but not Nox1, in PPHN PA and PASMC. We previously reported increased expression of the Nox2 activating protein p67 phox in fetal PPHN lambs relative to fetal controls (7), and we recently demonstrated that apocynin, an inhibitor of leukocyte Nox2 and a scavenger of H 2 O 2 in vitro (18), decreased p22 phox and p47 phox expression in ventilated PPHN lambs (46). While superoxide generated by Nox2 can contribute to elevated H 2 O 2 in PPHN, our siRNA data suggest that Nox4 is the major source of increased ROS in PPHN PASMC.…”
Section: Nox4 In Pphnmentioning
confidence: 97%
“…Recent studies demonstrated the increased NFjB activity in small pulmonary arterial lesions and in macrophages from explanted lungs of patients with idiopathic pulmonary arterial hypertension (22), and that inhibition of NFjB via pharmacological inhibition or delivery of a nanoparticle-mediated NFjB decoy attenuated monocrotaline-induced pulmonary arterial hypertension in rats (22,35). We previously reported increased expression of other NFjB target genes in PPHN, including inducible nitric oxide synthase (14), which may contribute to elevated levels of peroxynitrite in PPHN (46) and increase vasoconstriction of the neonatal pulmonary circulation (4,23). We suggest that the Nox4-induced NFjB activity may be involved in several dysregulated pathways in PPHN, and could be an important potential therapeutic target in PPHN.…”
Section: Nox4 In Pphnmentioning
confidence: 99%
“…Although the underlying mechanisms are incompletely understood, they involve impaired nitric oxide (NO) synthase (NOS)-mediated vasodilation and increased levels of reactive oxygen species (ROS) (23,43). PPHN lambs also exhibit elevated pulmonary vascular oxidant stress relative to control lambs (7,50), and recent studies have demonstrated improved oxygenation in ventilated PPHN lambs that received intratracheal antioxidants at birth (13,49,50). ROS may promote vasoconstriction directly and by impairing NO-mediated vasodilation (6,13,39), suggesting that the sources of increased ROS generation in PPHN are potential therapeutic targets.…”
mentioning
confidence: 99%
“…Finally, since NADPH oxidase was proved a major source of superoxide anions in pulmonary arteries in different models of PPHN (38, 60) and the treatment with NADPH oxidase inhibitor was proved effective in reducing ROS in pulmonary arteries of PPHN models (186), the associated therapy of rhSOD and NADPH oxidase may offer additive benefits and, therefore, deserves to be investigated for this purpose.…”
Section: Newborn Lung Polymorphisms Antioxidant Enzymesmentioning
confidence: 99%